2010
DOI: 10.1051/ps:2008031
|View full text |Cite
|
Sign up to set email alerts
|

On a Szegö type limit theorem, the Hölder-Young-Brascamp-Lieb inequality, and the asymptotic theory of integrals and quadratic forms of stationary fields

Abstract: Abstract. Many statistical applications require establishing central limit theorems for sums/integrals Mathematics Subject Classification. 60F05, 62M10, 60G15, 62M15, 60G10, 60G60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…It can be shown that the standard Taylor expansion methods based on the smoothed periodogram convergence results of type (3.4) and (3.5) with a general smoothing function g(λ; θ) and with the contaminated periodogram I T,X (λ) instead of I T,Y (λ), lead consistent and asymptotically normally distributed estimators of θ. We will not pursue this matter here (the details will be reported elsewhere), however, notice that in the special case of Whittle procedure, where g(λ; θ) = ∂ ∂ 1 f (λ,θ) · w(λ) the results of Anh et al [3], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26] concerning consistency and asymptotic normality of the Whittle minimum contrast estimators constructed on the basis of the periodogram I T,Y (λ), continue to hold without change for estimators calculated on the basis of the contaminated periodogram I T,X (λ), under appropriate assumptions imposed on the model Y (t) on the smoothing function g(λ, θ) and on the trend M (t).…”
Section: The Approach and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be shown that the standard Taylor expansion methods based on the smoothed periodogram convergence results of type (3.4) and (3.5) with a general smoothing function g(λ; θ) and with the contaminated periodogram I T,X (λ) instead of I T,Y (λ), lead consistent and asymptotically normally distributed estimators of θ. We will not pursue this matter here (the details will be reported elsewhere), however, notice that in the special case of Whittle procedure, where g(λ; θ) = ∂ ∂ 1 f (λ,θ) · w(λ) the results of Anh et al [3], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26] concerning consistency and asymptotic normality of the Whittle minimum contrast estimators constructed on the basis of the periodogram I T,Y (λ), continue to hold without change for estimators calculated on the basis of the contaminated periodogram I T,X (λ), under appropriate assumptions imposed on the model Y (t) on the smoothing function g(λ, θ) and on the trend M (t).…”
Section: The Approach and Resultsmentioning
confidence: 99%
“…Continuous versions of Whittle estimation procedure have been considered, for example, in Anh et al [3,4], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26].…”
Section: The Approach and Resultsmentioning
confidence: 99%
See 3 more Smart Citations